Effect of jet stretch in the fabrication of polyethersulfone hollow fiber spinning for water separation - Bolong, N.; Ismail, A. F.; Salim, M. R. (2007)
The effect of jet stretch on the morphology, pure water permeation and sodium chloride rejection of hollow fiber membranes is analyzed by varying the spinning take up speed. Polyethersulfone hollow fibers were spun using dry–wet spinning technique. The membrane formulation of PES/NMP/Water/PVPk10 is spun at constant extrusion rate of 3.0 cm3/ min. The fiber take up speed during spinning varied from 19.7 to 29.5 cms–1, revealed that the flux of hollow fiber membranes is minimal when the fiber take up speed is equivalent to the velocity of dope extrusion. At low jet stretch, the permeability of membranes is high with elevated ionic solutes rejection produced. The influence of elongation stress towards hollow fiber membranes morphology and its performance for water separation is also highlighted